1947
DOI: 10.1136/bmj.1.4506.677
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis as Complication of Diabetes Mellitus

Abstract: During the nineteenth century, when the incidence of and the mortality from pulmonary tuberculosis were much greater than at present, a large percentage of sufferers from diabetes mellitus died of coma, and most of those who survived this died of pulmonary tuberculosis. Publications towards the end of that century indicate that 50% of diabetics succumbed to pulmonary tuberculosis. For example, Windle (1883) Table I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1951
1951
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Epidemiologic studies indicate that diabetes mellitus (DM) is a significant risk factor for both acquisition of TB disease and increased disease severity . The original observations were noted more than half a century ago, but concerns have been heightened recently due to the rising rates of Type II DM worldwide . In a systematic review of observational studies with age‐adjusted estimates of the association of DM with active TB disease, 13 studies were identified with 1 786 212 participants and 17 698 cases of TB .…”
Section: Got Balance? Establishing Effective Anti‐tb Immunity By Targmentioning
confidence: 99%
“…Epidemiologic studies indicate that diabetes mellitus (DM) is a significant risk factor for both acquisition of TB disease and increased disease severity . The original observations were noted more than half a century ago, but concerns have been heightened recently due to the rising rates of Type II DM worldwide . In a systematic review of observational studies with age‐adjusted estimates of the association of DM with active TB disease, 13 studies were identified with 1 786 212 participants and 17 698 cases of TB .…”
Section: Got Balance? Establishing Effective Anti‐tb Immunity By Targmentioning
confidence: 99%
“…Specifically, the HIV epidemic has highlighted T cell function as an important component of immune protection. Besides HIV, there remains many other significant conditions in which the risk of Mtb acquisition and or progression from latent infection to active disease is increased (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes as an epidemiological risk factor for TB is wellreported (13). Spanning back to 1947, a review of diabetes and Mtb co-infection reported that 50% of diabetics succumbed to pulmonary TB (10). In recent years the epidemic has grown, with the number of individuals with Diabetes-TB overtaking those with HIV-TB (14); which can be attributed in part, to the positive impacts that antiretroviral therapy is having on reducing TB-HIV co-infection (15).…”
Section: Introductionmentioning
confidence: 99%
“…An adverse effect of diabetes mellitus (DM) on the host defense against tuberculosis (TB) has been recognized for over a century but has only recently been investigated in detail as DM rates have increased dramatically since the 1980s in low‐ and middle‐income countries where TB is already prevalent . Insulin‐resistant type 2 DM comprises 90% of the global cases of DM and a large proportion of the people afflicted with the dual TB/DM burden ; however autoimmune type 1 DM is also associated with TB susceptibility . This is unsurprising since both types of DM share a similar spectrum of other complications that develop as a consequence of chronic hyperglycemia .…”
Section: Introductionmentioning
confidence: 99%